The role of Tahfidzul Quran Program to Improve the Student Learning Outcomes in 7th Grade of Mts Nurul Iman Pomalaa District - Abdul Haris Nasution (Jurnal Teknologi Pendidikan Madrasah, 2022)
Memorizing the Qur'an is a way to remember verse by verse in the Qur'an, including fluency in reciting and the correctness of recitation, all of which must be memorized perfectly and completely. Based on several relevant studies regarding memorizing the Qur'an, it shows that there is a correlation for students who memorize the Qur'an in increasing their Intelligence Quotient.